Efforts to Increase Understanding of COVID-19 Screening in Assisted Reproductive Technology Services - Budihastuti, Uki Retno; Laqif, Abdurahman; Melinawati, Eriana; Prakosa, Teguh; Udiyanto, Hermawan; Priyanto, Heru; ., Darto; Ratnasari, Affi Angelia; Anggraeni, Asih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: The assisted reproductive technology (ART) program for examining infertile couples requires face-to-face with a doctor. This face-to-face examination for the ART program has a risk for the transmission of COVID-19 to all medical personnel and infertile couples who want to undergo the ART program. This study aims to understand pre- and post-test education about COVID-19 screening on ART services.Methods: A total of 50 infertile couples in the ART program are given education online. The use of online methods using the Zoom application due to the COVID-19 pandemic. Evaluation of the level of understanding using pre and post-test providing education. Data analysis was carried out using the SPSS 23 application.Results: Analysis of the level of understanding of pre-test and post-test education using the Wilcoxon test. Pre-test results were 69.90±12.05, post-test 73.00±10.83 with significance values p<0.001. Chi-Square test analysis results obtained p<0.001 and OR = 15.68.Conclusion: There was a significant increase in understanding of COVID-19 screening in the post-test education ART service via the Zoom application compared to pre-test education.